Analysis of Information Security Awareness of E-Commerce Users Among Micro Small Medium Enterprises - Muttaqin, Irham Khairul; Maesaroh, Syti Sarah; Herdiana, Oding (Jurnal Teknologi Informasi dan Pendidikan, 2024)
Information security is vital in today's digital era. Micro small medium enterprises are always required to survive with the unfavorable conditions. Through e-commerce, businesses can be helped to sell their products widely. Carelessness in managing information in e-commerce applications by business owners can cause great losses. In this article, the information security awareness of MSMEs will be analyzed using the Knowledge Attitude Behaviour method developed by Kruger-Kearney. The sample of respondents was taken using a purposive sampling technique where the criteria for respondents were categorized micro small medium enterprises owners and using e- commerce applications to sell their products. This article succeeded in analyzing, that the awareness of business owners was in a good category. The resulting score is 93 and is considered a high value. There are several factors that cause the high awareness score obtained, one of which is the training held by the state-owned creative house. This article can be developed for further research.